Heterologous desensitization of the cyclic AMP-independent glycogenolytic response in rat liver cells. - Bréant, B (1981)
Vasopressin and alpha-adrenergic agonists are known to be potent cyclic AMP-independent Ca2+-dependent activators of liver glycogen phosphorylase. When hepatocytes are pre-incubated with increasing concentrations of vasopressin or of the alpha-agonist phenylephrine, they become progressively unresponsive to a second addition of the respective agonist. The relative abilities of six vasopressin analogues and of five alpha-agonists to activate glycogen phosphorylase and to cause subsequent desensitization are highly correlated, indicating that the same vasopressin and alpha-adrenergic receptors are involved in both responses. About 5-times-higher peptide concentrations are needed to desensitize the cells than to activate their glycogen phosphorylase, whereas the concentrations of alpha-agonists required for the desensitization are only twice those needed for the activation of phosphorylase. The desensitization is not mediated by a perturbation in the agonist-receptor interaction. It is clearly heterologous, i.e. it is not agonist-specific, and must therefore involve a mechanism common to both series of agonists. The evidence for a role of Ca2+ movements or phosphatidylinositol turnover is briefly discussed.